Perceived self-efficacy of engineering students with regard to communication ability in impromptu speech task - Suradi, Noorsaiyidah; Ithnin, Fazidah; Yusof, Mohd Nizam; Tan, Poh Ee; Khoo, Linda Mei Sui (Kalahari Journals, 2022)
There were increasing attention be given to the notion of speaking self-efficacy and its impacts on language teaching and learning. Scholars have discovered indirect correlation between self-efficacy to task performance. Speaking self-efficacy was defined as individual’s awareness of his abilities to learn or perform the speaking task at the expected levels. However, many studies done on speaking self-efficacy focused on public speaking in general and were not narrowed down to impromptu speech. Drawing to fill in this gap, this study examines 3rd year Engineering students’ perceived self-efficacy with regard to communication ability in impromptu speech task. 246 engineering students enrolled in English for Professional Interaction course in Universiti Teknikal Malaysia Melaka were the respondents of this study. A quantitative study was adopted to measure the students’ self-efficacy from three dimensions namely ability, activity perception and aspiration. The study also investigates if there are different self-efficacy levels in relation to gender and hometown of the respondents. The key findings indicated that the respondents had considerably high level of self-efficacy with regard to their ability and perception towards impromptu speech task and were found to have high aspiration to be good English speakers. The study also reported significant difference in students' self-efficacy level between male and female as well as different self-efficacy levels between students from rural area and those from urban area. Exploring students’ level of self-efficacy in impromptu speech activity can provide insights towards developing their communication skills and shed more lights on pedagogical implications in language teaching and learning.